Manajemen Dana Zakat, Infaq, Dan Shodaqoh Pada Lazis Al-Haromain Cabang Kota Kediri - Sidanatul Janah (Sharia Business Management Study Program, Faculty of Economics and Islamic Business at IAIN Kediri, 2023)
Management of zakat, infaq and shodaqoh funds includes fundraising and distribution. Zakat, Infaq and Shodaqoh fundraising is an activity or process of how to collect Zakat, Infaq and Shodaqoh funds from muzzaki. This study aims to find out how the zakat collection strategy is carried out by the Amil Zakat Infaq and Shodaqoh Institution (LAZIS) Al- Haromain, the branch of the city of Kediri. This research is a field research, namely research conducted or held in certain places using descriptive-analytical methods. Data obtained through interviews with informants and document review. As for the results of this study it can be concluded that the Amil Zakat Infaq and Shodaqoh Institution (LAZIS) Al-Haromain uses its strategic position and takes advantage of technological advances to improve the perfoemance of collection and distribution of Zakat Infaq and Shadaqoh.